ISOLATION OF ANTIOXIDANT COMPOUNDS FROM ETHANOLIC EXTRACT OF ITCHY LEAVES (LAPORTEA DECUMANA (ROXB.) WEDD.) - Alifya, Nurhasna
Free radicals are unstable molecules or atoms that lack a pair of electrons, are highly reactive and seek to pair their electrons, can attack body cells, causing tissue damage. Antioxidants as a defense system against free radicals are substances that can prevent oxidative reactions by donating electrons to free radicals. External antioxidants are needed if the number of incoming free radicals exceeds the limit. The use of synthetic antioxidants can cause inflammation, liver damage, and increase the risk of carcinogenesis. Therefore, natural antioxidants are needed, which can come from plants. Itchy leaves (Laportea decumana (Roxb.) Wedd.) is an endemic plant from Papua known to have antioxidant properties. This study aims to isolate and characterize active antioxidant compounds from ethanol extracts of itchy leaves and determine the antioxidant activity of the extract using the DPPH scavenging method. The powdered plant material was extracted using a multistage maceration method with solvents in succession: nhexane, ethyl acetate, and 96% ethanol. The antioxidant properties of the extract were assessed both qualitatively and quantitatively using the DPPH scavenging method. This analysis revealed that the n-hexane extract of the itchy leaves has very weak antioxidant activity, while the ethanol extract has moderate potential. The ethanol extract of the itchy leaves was subjected to chlorophyll removal using a liquid-liquid extraction method (LLE), followed by a vacuum liquid chromatography (VLC) fractionation step. The selected fraction with antioxidant activity was purified using a preparative thin-layer chromatography (TLC) method. The purified product was tested for purity using single development TLC and two-dimensional TLC methods. The isolate was characterized using a TLC densitometry instrument. Based on the experimental results, it can be concluded that both the n-hexane and ethanol extracts of the itchy leaves (Laportea decumana (Roxb.) Wedd.) possess antioxidant activity as determined by the DPPH scavenging method. The ethanol extract of the itchy leaves has moderate antioxidant activity, while the n-hexane extract shows very weak potential. The isolated itchy leaves obtained from ethanol extract are suspected to be p-coumaric acid compound with a DPPH scavenging activity of 12.829 ± 0.846% at a concentration of 500 ?g/mL.